Ethnography of School Violence: A Cultural Perspective - Dhungana, Raj Kumar (Journal of Education and Research, 2020)
School education is largely universalised in Nepal, but schools are not yet free from different challenges like violence. This study aimed to explore how adolescents are experiencing school violence, how it affects the school life, and how Nepali public schools are responding to such violence. Exploring these aspects, as the theoretical basis, I used the idea of cultural violence (Galtung, 1990), critical theory of othering (Kumasiro, 2000) and some of the locally practiced perspectives.